Sex differences in quality indicator attainment for myocardial infarction: a nationwide cohort study - Wilkinson, Chris; Bebb, Owen; Dondo, Tatendashe B; Munyombwe, Theresa; Casadei, Barbara; Clarke, Sarah; Schiele, François; Timmis, Adam; Hall, Marlous; Gale, Chris P (Heart (British Cardiac Society), 2019)
AimTo investigate sex differences in acute myocardial infarction (AMI) guideline-indicated care as defined by the European Society of Cardiology (ESC) Acute Cardiovascular Care Association (ACCA) quality indicators.MethodsNationwide cohort study comprising 691 290 AMI hospitalisations in England and Wales (n=233 hospitals) from the Myocardial Ischaemia National Audit Project between 1 January 2003 and 30 June 2013.ResultsThere were 34.5% (n=238 489) women (median age 76.7 (IQR 66.3–84.0) years; 33.9% (n=80 884) ST-elevation myocardial infarction (STEMI)) and 65.5% (n=452 801) men (median age 67.1 (IQR 56.9–77.2) years; 42.5% (n=192 229) STEMI). Women less frequently received 13 of the 16 quality indicators compared with men, including timely reperfusion therapy for STEMI (76.8% vs 78.9%; p<0.001), timely coronary angiography for non-STEMI (24.2% vs 36.7%; p<0.001), dual antiplatelet therapy (75.4% vs 78.7%) and secondary prevention therapies (87.2% vs 89.6% for statins, 82.5% vs 85.6% for ACE inhibitor/angiotensin receptor blockers and 62.6% vs 67.6% for beta-blockers; all p<0.001). Median 30-day Global Registry of Acute Coronary Events risk score adjusted mortality was higher for women than men (median: 5.2% (IQR 1.8%–13.1%) vs 2.3% (IQR 0.8%–7.1%), p<0.001). An estimated 8243 (95% CI 8111 to 8375) deaths among women could have been prevented over the study period if their quality indicator attainment had been equal to that attained by men.ConclusionAccording to the ESC ACCA AMI quality indicators, women in England and Wales less frequently received guideline-indicated care and had significantly higher mortality than men. Greater attention to the delivery of recommended AMI treatments for women has the potential to reduce the sex-AMI mortality gap.